Adolescent gynae clinic - need of the day: a prospective study at a tertiary care centre - Jain, Anita; Singh, Dibya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To study common gynaecological problems in adolescent girls and to establish the need of adolescent clinic. Methods: A prospective study was conducted including 250 adolescent girls attending gynaecology OPD. Girls were evaluated by detailed history, thorough clinical examination and investigations such as haemogram, coagulation profile, hormonal assays, ultrasound examination of abdomen and pelvis, as and when indicated. Results: Majority of girls had complaints related to menstrual disorders i.e. 58.3%. Most common causes of menstrual abnormalities were dysfunctional uterine bleeding (42.85%) followed by polycystic ovarian syndrome (26.19%) and pelvic inflammatory disease (15.47%). Conclusions: Problems are specific to this age group, setting up of separate adolescent clinics is desirable of efficient management where they can be provided adequate privacy to discuss their problems openly.